COMPARISON OF HEBAL REMEDIES OF LEMONGRASS LEAVE (CYMBOPOGON CITRATUS) AND EUCALYPTUS OIL FOR RELIEF OF1ST-STAGE LABORPAIN AT SUNAN KUDUS ISLAMIC HOSPITAL - Silfana Nurul Chikmah; Nor Asiyah; Irawati (Lppm Unan, 2026)
Background: Labor pain is a unique challenge for both clinicians and mothers during labor. Non-pharmacological management of labor pain can not only reduce pain but also increase patient comfort during labor, using herbal remedies such as lemongrass and eucalyptus oil. Purpose: This study aims to determine the comparison of herbal remedies of lemongrass leaves (Cymbopogon Citratus) and Eucalyptus Oil on first-stage labor pain at RSI Sunan Kudus. Method: This type of research is a pre-experimental design with a two-group pretest and posttest approach. The population in this study was all mothers giving birth in the first stage at RSI Sunan Kudus, totaling 207 people, with a sample of all mothers giving birth in the first stage at RSI Sunan Kudus, totaling 51 people using a purposive sampling method. Data analysis was carried out using a t-test. Results: The results of the study obtained a p value of 0.243 (>0.05) statistically there was no significant difference in the pain scale between the groups that received Lemongrass Leaf Herbal Remedies (Cymbopogon Citratus) and those that received Eucalyptus Oil, both of which were able to control and help reduce the pain scale in the first stage of labor. Conclusion: There is no difference in the administration of herbal remedies of lemongrass leaves (Cymbopogon Citratus) and Eucalyptus Oil on first-stage labor pain at RSI Sunan Kudus.